1976
DOI: 10.1113/jphysiol.1976.sp011394
|View full text |Cite
|
Sign up to set email alerts
|

The nature of the pi1 colour mechanism of W.S. Stiles.

Abstract: SUMMARY1. The Ill colour mechanism was isolated by means of Stiles's auxiliary field technique: that it is H1l which is isolated is proven by both test and field action spectra.2. The fundamental mechanisms of human trichromatic colour vision must satisfy Grassmann's law of additivity. The hypothesis that H., is one of the three fundamentals is tested by experiments in which pairs (Al, /s2) of monochromatic adapting fields are mixed.3. When two fields with wave-lengths in the neighbourhood of its primary mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(31 citation statements)
references
References 22 publications
(25 reference statements)
0
31
0
Order By: Relevance
“…Shape invariance does hold photons are equal. The most thorough study of field additivity is that of Pugh (1976) who demonstrated that additivity held fo r 'IT! if both p-!…”
Section: Experimental Testsmentioning
confidence: 99%
“…Shape invariance does hold photons are equal. The most thorough study of field additivity is that of Pugh (1976) who demonstrated that additivity held fo r 'IT! if both p-!…”
Section: Experimental Testsmentioning
confidence: 99%
“…For the 4.0 log td background, this subject's SWS-cone-mediated sensitivities exhibited additional substantial day-to-day departures from the overall cyclic trend. This adaptation process probably can be identified with the "restoring force" postulated by Pugh and Mollon (1979) to reduce the second-site response polarization in the "yellow" direction caused by the contribution of LWS and0or MWS cone response to an SWS cone spectrally opponent pathway. Recently, Felius and Swanson (2003) showed that thresholds for detecting SWS-cone-mediated response were roughly twice as variable for background stimuli that strongly polarized a spectrally opponent "second site" (Pugh & Mollon, 1979) than for background stimuli that only weakly polarized that site.…”
Section: Additional Sources Of Individual Variations Of Visual Sensitmentioning
confidence: 96%
“…In addition, the ability of the retina to self-regulate its spectrally opponent response appears to differ quantitatively between individuals (Pugh & Mollon, 1979;Shapiro et al, 2003). Several hypothetical reasons were provided in the preceding Discussion, including the role of PMS, and the importance of the retinal locus tested.…”
Section: Roles Of Retinal Estrogen Receptorsmentioning
confidence: 98%
See 2 more Smart Citations